Hypothesis of Groundwater Flow Through Geological Structures in Guarani Aquifer System (GAS) Using Chemical and Isotopic Data - Gastmans, Didier [UNESP]; Mira, Andres; Kirchheim, Roberto; Vives, Luis; Rodriguez, Leticia; Veroslavsky, Gerardo; Marques, J. M.; Chambel, A. (Elsevier B.V., 2017)
Guarani Aquifer System (GAS) is one of the most important in South America shared by more than 9 million people living in Argentina, Brazil, Paraguay and Uruguay. Groundwater flow through GAS is controlled by the geological framework of the Parana and Chacoparanense sedimentary basins, dividing the aquifer in four groundwater flow compartments. The limit between north and southern compartment of the GAS is represented by the Rio Grande-Asuncion Arch (RGAA), a megastructure that represents a regional uplift. During long time the role played by this important geological structure over groundwater flow has remained a controversial question. Groundwater from the northern portion of the RGAA is characterized by elevated values of electrical conductivity (.> 1,500 mu S. cm(-1)), Na-Cl-SO4 type, and oversaturated with respect to calcite. On the other hand, despite their downgradient position, samples collected south of the structure, present low values of electrical conductivity (300-500 mu S. cm(-1)), Ca-HCO3 or Na-HCO3 types, and most samples are not saturated with respect to calcite. These differences allow inferring that groundwater flow through RGAA would not have continuity. Moreover, an important recharge zone could be stablished along the structure, partially responsible for the replenishment of the GAS in the southern compartment. (C) 2017 The Authors. Published by Elsevier B. V.
Keywords: Guarani Aquifer System; Groundwater Flow; Hydrochemistry; Geochemical Evolution